THE IMPACT OF EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF INTERNAL ENTREPRENEURSHIP (Third Sector Social Economic Review, 2017)
The purpose of this study is to examine the relationship between dimensions of emotional intelligence, evaluation of own emotions the evaluation of others' emotions, the use of emotions and regulation of emotions, and the performance of internal entrepreneurship. In order to determine the relationship between employees' emotional intelligence and internal entrepreneurship performances, correlation analysis and then a regression analysis were performed in the direction of the data of 126 questionnaires obtained from 4 and 5 star hotel employees. According to the results obtained from multiple regression analysis, it has been determined that evaluating their own feelings, evaluating others' feelings, use of feelings and regulation of emotions, which are dimensions of emotional intelligence, have no significant effect on internal entrepreneurship performance. There have been suggestions for future research.
Keywords: Emotional intelligence; Entrepreneurship; Internal entrepreneurship; Hotel employees; Organizational behavior